Prognostic importance of DNA-ploidy and S-phase fraction in endometrial cancer - Minckwitz, Gunter von; Kühn, W.; Kaufmann, Manfred; Feichter, Georg E.; Heep, Josef; Schmid, Hans; Bastert, Gunther (International journal of gynecological cancer, 1994)
On fresh frozen tumor tissue from 161 patients with endometrial cancer DNA-ploidy and S-phase fraction were measured in a prospective study to evaluate their prognostic and predictive value. All FIGO stage I or II patients had surgery and were included in an adjuvant trial comparing tamoxifen 30 mg p.o. versus medroxyprogesterone acetate 500 mg p.o. for 2 years versus no therapy. Diploid (DNA index (DI) ⩽ 1.1) tumors were found in 75%. S-phase fraction was elevated (>5%) in 46 (30%) of the patients. Significant correlations of DNA-ploidy and S-phase fraction were found with classical parameters such as stage, grade, histologic type and estrogen and progesterone receptor status. Patients with FIGO stage I aneuploid tumors showed significantly shorter disease-free interval (DFS) and overall survival (OAS). Recurrences and deaths occurred more often in tumors with raised S-phase fraction. In these early stages clinical outcome was worst if both factors were unfavorable. In multivariate analysis of stage I tumors DNA-ploidy and S-phase fraction were independent of grade, type and estrogen receptor status. Patients whose tumors had elevated S-phase fractions (>5%) gained more benefit from endocrine treatment than patients with low S-phase fractions. Patients with diploid and aneuploid tumors had prolonged DFS and improved OAS, if they had received adjuvant hormonal therapy. In endometrial cancer, DNA-ploidy and S-phase fraction are objective and reliable prognostic and predictive parameters which should be integrated into the clinical management.
Gesehen am 14.02.2024